2011
DOI: 10.1039/c1cp22238d
|View full text |Cite
|
Sign up to set email alerts
|

Arrhenius analysis of anisotropic surface self-diffusion on the prismatic facet of ice

Abstract: We present an Arrhenius analysis of self-diffusion on the prismatic surface of ice calculated from molecular dynamics simulations. The six-site water model of Nada and van der Eerden was used in combination with a structure-based criterion for determining the number of liquid-like molecules in the quasi-liquid layer. Simulated temperatures range from 230 K-287 K, the latter being just below the melting temperature of the model, 289 K. Calculated surface diffusion coefficients agree with available experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 36 publications
(64 reference statements)
9
53
0
Order By: Relevance
“…The onset temperature of disorder is found to depend on the crystal facet exposed to the vapour phase, for example on the basal plane, the first sign of interfacial disorder occurs about 100 K below the melting point, whereas on the prism plane disorder was observed around T m -80 K (Conde et al, 2008). The thickness of the disorder also shows systematic differences between the different crystal facets (Conde et al, 2008;Pfalzgraff et al, 2011) in agreement with 15 experimental observations (Sect. 2.3.2).…”
Section: Simulations Of Disorder On Pure Icesupporting
confidence: 86%
See 2 more Smart Citations
“…The onset temperature of disorder is found to depend on the crystal facet exposed to the vapour phase, for example on the basal plane, the first sign of interfacial disorder occurs about 100 K below the melting point, whereas on the prism plane disorder was observed around T m -80 K (Conde et al, 2008). The thickness of the disorder also shows systematic differences between the different crystal facets (Conde et al, 2008;Pfalzgraff et al, 2011) in agreement with 15 experimental observations (Sect. 2.3.2).…”
Section: Simulations Of Disorder On Pure Icesupporting
confidence: 86%
“…Molecular dynamics simulations show that a disordered layer develops spontaneously 5 at the free surface of ice at temperatures below the melting point (Bolton and Petterson, 2000;Picaud, 2006;Vega et al, 2006;Bishop et al, 2009;Neshyba et al, 2009;Pereyra and Carignano, 2009;Pfalzgraff et al, 2011). This has been observed regardless of the water model and the crystallographic plane exposed to the vapour phase ( Fig.…”
Section: Simulations Of Disorder On Pure Icementioning
confidence: 92%
See 1 more Smart Citation
“…Consequently, techniques sensitive to the outermost surface layers will always get a higher water mobility than methods looking at the bulk of the disordered interface or at grain boundaries; the differences may well span orders of magnitude. Molecular dynamics work by Pfalzgraff et al (2010Pfalzgraff et al ( , 2011 and Gladich et al (2011) confirmed the enhanced mobility of water molecules on free ice surfaces in the temperature range from 230 K to the melting point and provided more details Atmos. Chem.…”
Section: Diffusion Of Water At the Ice Surfacementioning
confidence: 88%
“…Two types of mechanisms take place in the QLL: in-plane diffusion and hopping among different layers. 17,49 A detailed characterization of the interlayer molecule exchange mechanism can be found in Pfalzgraff et al 17 :…”
Section: Dynamicsmentioning
confidence: 99%